Strategi Kepemimpinan Kepala Sekolah dalam Meningkatkan Prestasi Akademik Dan Non Akademik di MTs Negeri 7 Klaten - Natasya Nur Isnaini; Dartim Dartim (Cetta: Jurnal Ilmu Pendidikan, 2026)
The purpose of this study is to examine the principal's leadership strategy in improving academic and non-academic achievement at MTs Negeri 7 Klaten. This research is based on the understanding that the quality of a school is not only measured by the number of students, but also by the achievements obtained. As a qualitative research and using a phenomenological approach, this study collected information through interviews and documentation. Then, the collected data were analyzed using an interactive analysis model that includes data reduction, data presentation, and drawing conclusions. The findings of the study indicate that the principal of MTs Negeri 7 Klaten applies a transformational leadership strategy that emphasizes motivation, open communication, and collaboration of all members of the madrasah community. The strategy to improve academic achievement is implemented by increasing learning hours and extra-curricular olympiad programs. Meanwhile, the improvement of non-academic achievement is realized through strengthening the tahfidz program and extracurricular development. These various programs are supported by collaboration between teachers and external coaches to maximize student potential. The existence of class grouping based on student potential also strengthens the program's effectiveness. Therefore, the conclusion of the results of this research shows that the principal's leadership strategy contributes significantly to fostering a culture of achievement in the madrasah. Structured planning, open communication, and empowerment of all school components are the main factors in improving academic and non-academic achievements at MTs Negeri 7 Klaten.